Modeling of the flow stress behavior and microstructural evolution during hot deformation of Mg–8Al–1.5Ca–0.2Sr magnesium alloy - Xiao Liu; Luoxing Li; Biwu Zhu (Journal of Magnesium and Alloys, 2014)
Hot compression tests of Mg–8Al–1.5Ca–0.2Sr magnesium alloy were performed on the Gleeble-1500 machine at temperatures of 300, 350, 400, and 450 °C and strain rates of 0.01, 0.1 and 1 s−1. The flow stress behavior and microstructural evolution were followed. The work hardening was derived according to the Laasraoui–Jonas model. An improved approach, which considered the influence of yield stress on flow stress and the effect of grain boundary (GB) migration on the evolution of dislocation density during compression, was used to simulate the microstructural evolution, the flow stress and the volume fraction recrystallized of Mg–8Al–1.5Ca–0.2Sr magnesium alloy. The simulated results are in good agreement with experimental results.